Folate vitamers in the Australian green plum: Through growth and ripening and across locations - Fyfe, Selina; Hong, Hung; Schirra, Horst Joachim; Smyth, Heather E.; Sultanbawa, Yasmina; Rychlik, Michael (Frontiers in Nutrition, 2022)
The green plum is a native fruit of Australia that grows on the tree Buchanania obovata. This study aimed to confirm the high level of folate in green plums by analysing a large number of ripe samples from multiple locations and to understand how folate vitamers change as the fruit grows through maturity stages. This study analysed green plums for five vitamers of folate, H4folate, 5-CH3-H4folate, 5-CHO-H4folate, 10-CHO-PteGlu and PteGlu (folic acid) using a stable isotope dilution assay on a liquid chromatograph mass spectrometer (LC-MS). Green plums were tested from four locations, two harvests and five maturity stages. Another 11 ripe samples, each from different tree clumps from one location, were also tested as were ripe red-coloured green plums. The results show the 5-CH3-H4folate in green plum increases and accumulates in the fruit through development, ripening and senescence. The ripe green plums contain between 82.4 ± 5.5 and 149.4 ± 10.7 µg/100g Fresh Weight (FW). The red-coloured green plums are even higher in folate, with total folate measured as 192.5 ± 7.0 and 293.7 ± 27.4 µg/100g FW, and further analysis of them is suggested. There is some variation in amounts of folate between fruit from different locations and sets of trees, but all ripe green plums tested are considered good dietary sources of folate.